(Re)Collections of a “Piccola Streghina” from the Heart of the Mediterranean: Gender and Class Consciousness in Grazia Deledda’s Folkloric Writings - Sottilotta, Elena Emma (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
Nobel Prize winner in Literature in 1926, at the dawn of her literary career, Grazia Deledda (1871-1936) published several folkloric writings and ethnographic sketches based on tales and popular traditions that she personally collected among the members of the lower classes in Sardinia, an aspect of her production which has received considerably less critical attention in comparison with the scholarly scrutiny that has been devoted to her work as a novelist. Similar to other nineteenth-century female folklorists, Deledda promoted herself as a Sardinian collector in a complex social context and at a historical juncture when coming out in the public sphere was still unconventional for a woman. Nearly a century after her recognition as a Nobel Prize winner, it is important to acknowledge that she was not only a talented novelist but also a scrupulous divulgator of insular traditions. Hence, this article explores her positionality as a folklorist in her youth and some of the challenges she faced in gathering and publishing popular traditions in late nineteenth-century journals such as Natura ed Arte and Rivista delle tradizioni popolari italiane, under the mentorship of Angelo De Gubernatis. This article places emphasis on Deledda’s gender and class consciousness at this early stage of her life through an examination of her private correspondence with De Gubernatis and through a critical analysis of the first sketch that she published in Natura ed Arte, titled “La donna in Sardegna”. Although this piece is often listed amid her folkloric writings without much relevance attached to it, it shows an awareness of multiple social perspectives and touches upon several issues that characterised Deledda’s subsequent literary production, namely her ideological relationship with lower-class women, her self-identification as a middle-class woman, and the increasing consciousness of her mediating role between the prejudiced image of Sardinia in the Italian mainland and the more accurate picture that she wished to convey to the continental readership.